Analysis And Comparison Of Airfoil-Polar Prediction Methods For Vertical-Axis Turbines - Goh, Su Teng (Universiti Sains Malaysia, 2021)
The numerical method used to analyse the vertical-axis turbine (VAT) performance in this study utilized the lifting line theory coupled with free vortex wake (LLTFVW). This method computes the blade forces from the tabulated airfoil lift and drag coefficients. The rotating axis of the blades of VAT is perpendicular to the wind stream leading to the blade experiencing a wider range of incidence angle than horizontal-axis turbine (HAT). Thus, full-range airfoil data is required to compute the turbine performance of VAT. The polar data can be obtained experimentally, but only for a limited range of angle of attack due to the high experimental costs and the limitations of specific wind turbines. A general approach for the polar extrapolation is applying curve fits generalisation to the experimental measured data. The full-range polar data obtained from QBlade is dependent on the prediction model used, which ultimately affects the simulated performance on the turbine. Hence, the present study had simulated and investigated the accuracy of full-range polar data and its effects on turbine performance through the Viterna and Montgomerie polar-extrapolation techniques in QBlade. This paper also performed optimization tests on the LLT simulation and a validation test with available simulation data to improve the reliability of the simulation data because the parameterization of the LLT simulation in QBlade involves numerous complicated settings. The turbine design used for the simulation is with a single blade of NACA 0018 airfoil. A focus is set on achieving high robustness and computational efficiency. From this study, a good agreement with the experimental and numerical polars data from the literature can be found based on aerodynamic characteristics of airfoil and turbine performance. The simulation results of this study have also been demonstrated to be reliable for future use.